1998
DOI: 10.1016/s0020-7292(98)00121-0
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome of elderly low-risk nulliparae

Abstract: After proper selection during pregnancy, the elderly nullipara under the care of a midwife does not have an increased risk of fetal distress or other emergency factors, compared to the younger nullipara. However, high referral rates during labor - both of younger and older women - were observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 18 publications
0
10
0
8
Order By: Relevance
“…Older women more commonly have pregnancy complications such as preterm delivery, multiple gestation, fetal malposition, placenta praevia and medical illness that increase the rate of operative delivery. Smit et al 21 found no increased risk for women ‡35 years of age for failure to progress in the first and the expulsive second stage of labour, but this study concerned a low-risk population and did not differentiate ages over 35 years. However, other authors reported older maternal age to be associated with protracted labour, Caesarean section and increased rates of vaginal operative delivery, 15,22 and have suggested a continuous decrease in myometrial function with increasing age.…”
Section: Discussionmentioning
confidence: 75%
“…Older women more commonly have pregnancy complications such as preterm delivery, multiple gestation, fetal malposition, placenta praevia and medical illness that increase the rate of operative delivery. Smit et al 21 found no increased risk for women ‡35 years of age for failure to progress in the first and the expulsive second stage of labour, but this study concerned a low-risk population and did not differentiate ages over 35 years. However, other authors reported older maternal age to be associated with protracted labour, Caesarean section and increased rates of vaginal operative delivery, 15,22 and have suggested a continuous decrease in myometrial function with increasing age.…”
Section: Discussionmentioning
confidence: 75%
“…However, AMA alone in otherwise low risk pregnancies has been associated with nearly as good pregnancy outcomes as in younger women and according to some studies maternal age alone is not a risk factor explaining the adverse outcomes, but associated with other risk factors like hypertension and diabetes may account for the results [13,14]. Co-existing risks accompanied with the ageing process jeopardize the outcome much more than in younger age groups, as we have shown previously in the case of smoking women and women affected by preeclampsia, both having been complicated by advanced age [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Naqvi MM et al, Smit S et al and Adashek et al also showed a higher incidence of caesarean section in elderly nulliparous women. [20][21][22] There were 69 cases of elective caesarean section in the study group (36%) compared to 12 cases in the control group (6%). The major indications for elective caesarean section was elderly primi having some complications and cephalopelvic disproportion for the elderly group and placenta previa for the control group; whereas that for emergency procedures was failed induction in both the groups.…”
Section: Discussionmentioning
confidence: 99%